Tindak Tutur Ilokusi dalam Khotbah Idul Adha di Alun-Alun Kabupaten Sragen Tahun 2024 - Hidayati, Tri Yanti Nurul; Farhah, Eva; Arifuddin, Arifuddin; Arummi, Afnan; Nugraha, Reza Sukma; Luthfi, Khabibi Muhammad; Anis, Muhammad Yunus; Ridwan, Muhammad (JILSA (Jurnal Ilmu Linguistik dan Sastra Arab), 2024)
Language is a means of communication used by people to interact. There are two types of communication, namely one-way communication and two-way communication. Sermons are an example of one-way communication. This study discusses the forms and functions of illocutionary speech acts in the Eid al-Adha sermon at Sragen Regency Square in 2024. The purpose of this study is to describe the forms and functions of illocutionary speech acts included in the Eid al-Adha sermon at Sragen Regency Square in 2024. The subject of this study is the illocutionary speech act in the Eid al-Adha sermon. The data in this study are speeches containing illocutionary acts in the Eid al-Adha sermon. This study uses the pragmatic equivalent method, which is recording and note-taking techniques. The results of this study show that the illocutionary speech acts used by khaṭīb during his sermon are assertive, directive, commisive, expressive, and declarations. The expressiveness of the Eid al-Adha sermon is to suggest, confirm, and inform. The directive function found is to request. The commisive function found is to guarantee. The expressive function is to praise. At the same time, the explanatory form of the Eid al-Adha sermon has a state function. In the Eid al-Adha sermon, utterances in the form of declarative sentences are frequently used. Those that are rarely used are commisive forms.